Blended Module‐Based Teaching in Biostatistics and Research Methodology: A Retrospective Study with Postgraduate Dental Students - Varghese, Sheeja Saji; Ramesh, Asha; Veeraiyan, Deepak Nallaswamy (Journal of dental education, 2019)
Information technology has stimulated efforts to reform teaching methods in dental education. Most of these efforts involve a shift from conventional mode to the more technology‐savvy and student‐centered approach. The aim of this study was to compare postgraduate dental students' academic performance using two teaching methodologies (video‐based learning and blended module‐based learning) in a biostatistics and research methodology course in a master's program at a dental college in India. This retrospective study involved two groups of students enrolled in the master's program with different years of admission: Group I in 2013‐14 (n=80) and Group II in 2015‐16 (n=80). Group I students learned the subjects with video‐based learning, whereas Group II students were taught using a blended module program using a small‐group learning system called Process‐Oriented Guided Inquiry Learning (POGIL). The students' final course evaluation (summative assessment) and formative assessment (during course assessments) were compared for the two groups. The students' final course evaluation was derived from an end‐of‐year written examination, whereas the formative assessment was recorded with written tests and projects during the course. In the results, the summative assessment did not show a significant difference between Group I (68.2±13.4) and Group II (66.4±11.9) (p=0.39). The formative assessment showed a significant difference (p<0.001) in favor of the Group II students. In this study, the blended module‐based teaching produced similar scores on the final exam to the video‐based lectures, but it produced significantly better results on the in‐course assessments. The latter finding could be attributed to the incorporation of small‐group learning and POGIL.